New Methods for Surgical Treatment of Perthes Disease in Children - M. DJuraev, Akhrarbek; J. Khalimov, Ravshan (International Journal of Psychosocial Rehabilitation, 2020)
The treatment of Perthes disease in children and adolescents is a complex and unresolved problem. The various methods of conservative and surgical treatment used in most clinical observations do not allow to obtain the desired results. At the same time, the number of unsatisfactory outcomes of surgical treatment remains very high (18–27%). The consequence of this is the early disability of a significant number of patients of the most working age. In recent years, there has been a clear trend towards the use of surgical methods of treating this pathology. However, inadequate surgical tactics often give a high percentage of unsatisfactory outcomes. The choice of treatment method for patients with Perthes disease is still debatable.